Autophagy Promoted the Degradation of Mutant ATXN3 in Neurally Differentiated Spinocerebellar Ataxia-3 Human Induced Pluripotent Stem Cells - Ou, Zhanhui (Biomed Res Int, 2016)
Spinocerebellar ataxia-3 (SCA3) is the most common dominant inherited ataxia worldwide and is caused by an unstable CAG trinucleotide expansion mutation within the ATXN3 gene, resulting in an expanded polyglutamine tract within the ATXN3 protein. Many in vitro studies have examined the role of autophagy in neurodegenerative disorders, including SCA3, using transfection models with expression of pathogenic proteins in normal cells. In the current study, we aimed to develop an improved model for studying SCA3 in vitro using patient-derived cells. The patient-derived iPS cells presented a phenotype similar to that of human embryonic stem cells and could be differentiated into neurons. Additionally, these cells expressed abnormal ATXN3 protein without changes in the CAG repeat length during culture for at least 35 passages as iPS cells, up to 3 passages as neural stem cells, and after 4 weeks of neural differentiation. Furthermore, we demonstrated that neural differentiation in these iPS cells was accompanied by autophagy and that rapamycin promoted autophagy through degradation of mutant ATXN3 proteins in neurally differentiated spinocerebellar ataxia-3 human induced pluripotent stem cells (p < 0.05). In conclusion, patient-derived iPS cells are a good model for studying the mechanisms of SCA3 and may provide a tool for drug discovery in vitro.